Homeopathic Medicine Versus Traditional Chinese Medicine: An Analytical Overview - Sheikh Faruque Elahee; Huijuan Mao; Fatema Zohra; Sheikh Muhammad Bin Faruque; Xueyong Shen (Wolters Kluwer Health/LWW, 2020)
Conventional homeopathy and traditional Chinese medicine (TCM) are two popular alternative systems of medicine, which are practiced also in many countries outsidethe countries of origin. Homeopathy originated in Germany in the 19th century and spread throughout the world in spite of antagonism by theorthodox practitioners. It is a holistic medicine based on the principles of treatment where the remedy and the disease have similar symptoms,applies a single potentized medicine at a time, in minimum dose. TCM, also a holistic medicine originating in ancient China about 3000 years ago, has been developed and practiced through centuries till today as one of the most popular alternative medicines in the world. Both the systems ofmedicine have many differences in theories, principles and practices, but they have some important aspects in common. Both are holistic in approach,treating the whole patient, not the affected organs only; focusing on stimulating the intrinsic life principle to bring order, and on homeostasis and balance in the organism. In therapeutics, they may advantageously be applied as adjuvant to each other, producing synergistic effects.